The National Cohort of Esophageal Cancer-Prospective Cohort Study of Esophageal Cancer and Precancerous Lesions based on High-Risk Population in China (NCEC-HRP): study protocol - Chen, Ru (BMJ Open, 2019)
INTRODUCTION: Oesophageal cancer (OC) is one of the most common cancers worldwide and about 50% of all new cases occurred in China. Population-based screening has been conducted in high-risk areas in China since 1970s, however, a few factors have limited the integration of the results from previous studies and the sharing of existing resources, such as the difference in screening methods and protocols, inconsistencies in questionnaires for risk factors investigation, lack of standards for sample collection and incomplete follow-up information. METHODS AND ANALYSIS: The National Cohort of Esophageal Cancer-Prospective Cohort Study of Esophageal Cancer and Precancerous Lesions based on High-Risk Population (NCEC-HRP) is a prospective cohort study of OC screening based on high-risk population in China supported by the National Key R&D Programme. Eight areas located at eastern, central and western China are selected as screening centres to represent three economical-geographical regions. All local residents aged 40–69 years in the selected areas are invited to take endoscopic examination and risk factors investigation unless they meet the exclusion criteria. The recruitment began on June 2017 and a total of 100 000 participants will be enrolled by December 2020 and all subjects will be followed for a long time. This study is designed as open-ended and has broad research aims. Summary statistics for baseline information will be reported after the completion of recruitment. We will develop a series of standards and guidelines for OC screening during the study. An open and shared research platform linked with epidemiological databases and biobank will be built up for further research. ETHICS AND DISSEMINATION: The study is approved by the Ethics Committee of Cancer Institute and Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College (approval number 16-171/1250). The findings of the study will be disseminated through scientific peer-reviewed journals as well as the public via the study website (http://www.ncec-china.cn). TRIAL REGISTRATION NUMBER: ChiCTR-EOC-17010553; Pre-results.